Drug induced haematotoxicity - S. S. Postnikov; M. N. Kostylyova; A. N. Gratsianskaya; A. E. Ermilin (Безопасность и риск фармакотерапии, 2018)
The main types of hematological complications related to ongoing pharmacotherapy - (different types of cytopenia, as well as coagulopathy) are presented. The risk factors and mechanisms of development of these disorders are discussed. The authors emphasize the importance of awareness by doctors of the existence of drug induced pathology (disease) as a separate type of iatrogeny.